2005
DOI: 10.1063/1.2140443
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic four-point probe based on SU-8 cantilevers

Abstract: A microscopic four-point probe ͑4PP͒ for resistivity measurements on thin films was designed and fabricated using the negative photoresist SU-8 as base material. The device consists of four microscopic cantilevers, each of them supporting a probe tip at the extremity. The high flexibility of SU-8 ensures a stable electrical point contact between samples and probe tip with all four electrodes even on rough surfaces. With the presented surface micromachining process, 4PPs with a probe-to-probe spacing of 10-20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Genolet et al [4] have already demonstrated the feasibility of such a fabrication process, presenting a reduced number of steps and therefore saving time and reducing cost production. Other authors [5,6] have also studied the advantages of cantilever sensors fabrication based on polymer technology, reaching similar conclusions.…”
Section: Introductionmentioning
confidence: 54%
“…Genolet et al [4] have already demonstrated the feasibility of such a fabrication process, presenting a reduced number of steps and therefore saving time and reducing cost production. Other authors [5,6] have also studied the advantages of cantilever sensors fabrication based on polymer technology, reaching similar conclusions.…”
Section: Introductionmentioning
confidence: 54%
“…It can readily be applied to the fabrication of microcoils, similar to those shown in Fig. 7, for electron spin resonance microscopy and integrated four-point microprobes for electrical characterization of metallic thin films, etc., [21]. The described technology opens the way to further advances in the field of functional polymer sensors combined with surface microfabrication techniques.…”
Section: Discussionmentioning
confidence: 97%
“…Various materials with lower Young's modulus (<4 GPa) and larger damping coefficient, e.g. SU-8 photoresist [17], [18], have been proposed to fabricate AFM probes [17], [19]- [22], which can enable fast detection and characterization [23], [24] of fragile materials such as polymer semiconductors [25] or biological cells [26]. Therefore, polymer materials have become a new material for the preparation of fast-responding AFM probes [24], [27], [28].…”
Section: Introductionmentioning
confidence: 99%